2013
DOI: 10.1016/j.kjms.2012.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between changes in leptin and insulin resistance levels in obese individuals following weight loss

Abstract: Obesity can augment insulin resistance (IR), leading to increased risk of diabetes and heart disease. Leptin, ghrelin, and various fatty acids present in the cell membrane may modulate IR. In this study, we aimed to investigate the impact of weight loss on IR, serum leptin/ghrelin levels, and erythrocyte fatty acids, and studied the associations between changes in these variables. A total of 35 obese (body mass index ≥ 27) adults participated in a weight loss program for 3 months. IR was assessed using homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The association between the decrease in leptin and the improvement in HOMA-index with CR (see results) was also shown with weight loss in obese patients [34]. Our results therefore indicate that even in mostly lean or slightly overweight subjects a diet-induced decrease in leptin is associated with improved insulin sensitivity.…”
Section: Discussionsupporting
confidence: 79%
“…The association between the decrease in leptin and the improvement in HOMA-index with CR (see results) was also shown with weight loss in obese patients [34]. Our results therefore indicate that even in mostly lean or slightly overweight subjects a diet-induced decrease in leptin is associated with improved insulin sensitivity.…”
Section: Discussionsupporting
confidence: 79%
“…This is in agreement with recent studies reporting the strong association of leptin with insulin resistance. 23 In adipocytes, leptin inhibits glucose uptake, impairs lipogenesis, and inhibits lipolysis. 24 But in hepatocytes, leptin triggers insulin-like effects through regulating insulin signalling pathways; thus making the hepatocytes more sensitive to insulin.…”
Section: Discussionmentioning
confidence: 99%
“… 14 In addition, obesity can alter adipokine production, which regulates body weight, appetite and energy expenditure and modulates IR. For example, leptin, which controls TNF-α production, 15 has been implicated in the modulation of glucose homeostasis and IR; 16 adiponectin, which is the most abundantly secreted protein by white adipose tissue, has a well-known inverse relationship with adiposity and risk of T2DM. Adiponectin is also inversely associated with IR in human populations and some studies have demonstrated that adiponectin exerts an insulin-sensitizing effect; 17 elevated resistin has been shown in obese rodents.…”
Section: Introductionmentioning
confidence: 99%